The Effects of Climate Change on Economic Activity in Maine: Coastal York County Case Study - Colgan, Charles; Merrill, Samuel (Maine Policy Review, 2008)
Climate change can have significant ramifications for Maine’s economy. If short-term projections for the next century are accurate, at minimum sea level rise will become increasingly noticeable in association with more severe and destructive coastal storms. Charles Colgan and Samuel Merrill evaluate risk estimates by presenting a case study of the projected consequences of sea level rise and coastal storm damage on the economy of the state’s most vulnerable area, York County’s coastal communities.
Keywords: York County Maine; climate change; sea level rise; climate change economic impacts